2022
DOI: 10.3389/fmolb.2022.811145
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Model of Sub-Plasmalemmal Ca2+ Microdomains Evoked by T Cell Receptor/CD3 Complex Stimulation

Abstract: Ca2+ signalling plays an essential role in T cell activation, which is a key step to start an adaptive immune response. During the transition from a quiescent to a fully activated state, Ca2+ microdomains of reduced spatial and temporal extents develop in the junctions between the plasma membrane and the endoplasmic reticulum (ER). These microdomains rely on Ca2+ entry from the extracellular medium, via the ORAI1/STIM1/STIM2 system that mediates store operated Ca2+ entry Store operated calcium entry. The mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…158,159 Research has shown that the production of the inositol 1,4,5-trisphosphate (IP 3 ) is associated with the inhibition of cytotoxic T cells (CTL) killing function by Treg factors, indicating that the reduction of the IP 3 concentration leads to a decrease in T cell receptor (TCR)-dependent intracellular Ca 2þ concentration. [160][161][162] However, the process of regulating the calcium ion concentration through the IP3 protein pathway is complex and slow. Therefore, researchers have proposed the use of optogenetics to increase Ca 2þ concentration, which can rapidly reduce the local Treg factor influence on CTL and relieve the immunosuppression of the microenvironment.…”
Section: Cancer Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…158,159 Research has shown that the production of the inositol 1,4,5-trisphosphate (IP 3 ) is associated with the inhibition of cytotoxic T cells (CTL) killing function by Treg factors, indicating that the reduction of the IP 3 concentration leads to a decrease in T cell receptor (TCR)-dependent intracellular Ca 2þ concentration. [160][161][162] However, the process of regulating the calcium ion concentration through the IP3 protein pathway is complex and slow. Therefore, researchers have proposed the use of optogenetics to increase Ca 2þ concentration, which can rapidly reduce the local Treg factor influence on CTL and relieve the immunosuppression of the microenvironment.…”
Section: Cancer Researchmentioning
confidence: 99%
“…Research has shown that the production of the inositol 1,4,5‐trisphosphate (IP 3 ) is associated with the inhibition of cytotoxic T cells (CTL) killing function by Treg factors, indicating that the reduction of the IP 3 concentration leads to a decrease in T cell receptor (TCR)‐dependent intracellular Ca 2+ concentration 160–162 . However, the process of regulating the calcium ion concentration through the IP3 protein pathway is complex and slow.…”
Section: Applications Of Optogenetics In Various Fieldsmentioning
confidence: 99%
“…In this study, the channel locations in the PM, ER or mitochondrial membranes are not specified and Ca 2+ fluxes are homogeneously distributed across these membranes. The detailed impact of Ca 2+ channel locations on the spatio-temporal profiles of Ca 2+ changes inside the ER-PM junctions were analyzed in 1D by ( 18 ) and modelled in 3D by ( 61 , 62 ) and ( 63 , 64 ). In this section, we describe these models and their main relying assumptions, while their physiological outcomes are presented in the next section.…”
Section: Er-pm Ca 2+ Microdomains In T Cells: Mode...mentioning
confidence: 99%
“…Although NAADP mobilizes lysosomal Ca 2+ ( 67 ), the involvement of this organelle in the formation of T cells Ca 2+ microdomains remains to be established ( 68 ). Instead of considering [IP 3 ] and [NAADP] explicitly, their effects can be modelled by changing the opening states of their receptors directly ( 63 , 64 ). This simplification is however not valid when considering the transition from local to global Ca 2+ signaling which involves considering diffusion and metabolism of the messengers.…”
Section: Er-pm Ca 2+ Microdomains In T Cells: Mode...mentioning
confidence: 99%
See 1 more Smart Citation